Cognitive‐self consciousness and metacognitive beliefs: Stress sensitization in individuals at ultra‐high risk of developing psychosis. (7th September 2012) - Palmier‐Claus, J. E.; Dunn, G.; Taylor, H.; Morrison, A. P.; Lewis, S. W.
<x xml:space="preserve">Abstract</x> Objective: Metacognitive beliefs (MCB) may guide information and attention processes, increasing affective and symptomatic reactions to stressful events. Cognitive self‐consciousness (CSC; i.e., a preoccupation with one's thoughts) may increase awareness of MCB, potentially triggering the onset of psychotic symptoms. This study tested the hypotheses that (1), MCB would moderate affective and symptomatic reactions to stress in individuals at ultra‐high risk (UHR) of developing psychosis, and (2), greater CSC would precede worsening in psychotic symptoms in individuals with strong MCB. Method: Twenty‐seven individuals at UHR of developing psychosis completed a self‐report diary when prompted by an electronic wristwatch several times each day for 6 days (experience sampling). Results: MCB moderated the association between affective, but not symptomatic, responses to social stress. CSC preceded the subsequent occurrence of hallucinations in individuals who reported strong beliefs about the need to control their thoughts. Conclusions: The data suggest that MCB sensitize an individual to social stressors. CSC may represent times where an individual is aware that their thoughts are uncontrollable, and therefore contradicting their MCB, motivating them to make an external attribution. The findings have implications for improving the effectiveness of interventions for people experiencing hallucinations. Practitioner Points Cognitive self‐consciousness may precede the onset of hallucinations in individuals with a strong belief that they need to control their thoughts. Metacognitive beliefs may increase emotional reactions to everyday irritations and hassles. Limitations Only 27 individuals were included in the final analysis. Causality could not be established.